2021
DOI: 10.3892/ijmm.2021.4895
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide C attenuates lipopolysaccharide‑induced acute lung injury by inhibiting inflammation via regulating the CD40/NF‑κB signaling pathway

Abstract: Excessive lung inflammation caused by endotoxins, including lipopolysaccharide (LPS), mediates the detrimental effects of acute lung injury (ALI), as evidenced by severe alveolar epithelial cell injury. CD40, a member of the tumor necrosis factor receptor superfamily, serves as a central activator in triggering and transducing a series of severe inflammatory events during the pathological processes of ALI. Ginkgolide C (GC) is an efficient and specific inhibitor of CD40. Therefore, the present study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Some studies have showed potential benefits of beta-ionone in human health regarding important pharmacological activities: antiinflammatory, anti-cancer, antibacterial, antifungal, and ginkgolide c has been reported to display various pharmacological actions of reducing lipid accumulation, increasing lipolysis, inhibiting inflammation, anti-cancer. [45][46][47] Meanwhile, jasmonic acid has showed a broad spectrum of activity, anti-cancer, anti-inflammatory and anti-ageing. 48 These secondary metabolites may be the material basis for the difference in efficacy between PGn and PGb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have showed potential benefits of beta-ionone in human health regarding important pharmacological activities: antiinflammatory, anti-cancer, antibacterial, antifungal, and ginkgolide c has been reported to display various pharmacological actions of reducing lipid accumulation, increasing lipolysis, inhibiting inflammation, anti-cancer. [45][46][47] Meanwhile, jasmonic acid has showed a broad spectrum of activity, anti-cancer, anti-inflammatory and anti-ageing. 48 These secondary metabolites may be the material basis for the difference in efficacy between PGn and PGb.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids, for example, contain beta‐ionone, ginkgolide c, jasmonic acid, alpha‐curcumene, capsidiol, and citraconic acid, etc. Some studies have showed potential benefits of beta‐ionone in human health regarding important pharmacological activities: anti‐inflammatory, anti‐cancer, antibacterial, antifungal, and ginkgolide c has been reported to display various pharmacological actions of reducing lipid accumulation, increasing lipolysis, inhibiting inflammation, anti‐cancer 45‐47 . Meanwhile, jasmonic acid has showed a broad spectrum of activity, anti‐cancer, anti‐inflammatory and anti‐ageing 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The lung injury score was applied to evaluate the severity of lung injury as previously described [ 23 ]. According to the thickness of alveolar wall, the amount of inflammatory infiltration, and the level of hemorrhaging, the lung score was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…A nuclear and cytoplasmic protein extraction kit (Beyotime Institute of Biotechnology) was applied to extract the cytoplasmic and nuclear proteins as previous described [ 23 ]. And a BCA assay kit was applied to determine the protein concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation